Study on a joint multiple layer restoration scheme for IP over WDM networks. - Yang Qin (IEEE Network : the magazine of global information exchange)
In this article we investigate the problem of a restoration scheme for IP over WDM networks. Network reliability is gaining importance with the huge volume of traffic carried by such networks. Providing survivability at the optical layer is inherently attractive, but raises many questions and challenges, given the characteristic of optical aggregated lightpath and relatively coarse traffic granularity. The emergence of MPLS and its extension, MPλS, opens up new possibilities for developing simple integrated protection/restoration schemes that can be coordinated at both the IP and optical layers . This article first presents an overview of existing MPLS/MPλS recovery mechanisms. Then we propose a joint two-layer recovery scheme for IP-centric WDM-based optical networks where the optical layer takes the recovery actions first, and subsequently the upper IP layer initiates its own recovery mechanism, if the optical layer does not restore all affected services. A simulation-based analysis shows the benefits of the proposed two-layer recovery scheme over single-layer recovery schemes. We demonstrate the advantages of finer granularity in IP layer recovery and the effectiveness in speed on the optical layer. The impact of several network parameters on recovery performance is also studied in the paper.